Decreased nesting behavior, selective increases in locomotor activity in a novel environment, and paradoxically increased open arm exploration in Neurogranin knockout mice - Ryuichi Nakajima; Satoko Hattori; Teppei Funasaka; Freesia L. Huang; Tsuyoshi Miyakawa (Wiley, 2021)
Abstract Aims Neurogranin (NRGN) is a postsynaptic protein kinase substrate that binds calmodulin in the absence of calcium. Recent studies suggest that NRGN is involved in neuropsychiatric disorders, including schizophrenia, ADHD, and Alzheimer's disease. Previous behavioral studies of Nrgn knockout (Nrgn KO) mice identified hyperactivity, deficits in spatial learning, impaired sociability, and decreased prepulse inhibition, which suggest that these mice recapitulate some symptoms of neuropsychiatric disorders. To further validate Nrgn KO mice as a model of neuropsychiatric disorders, we assessed multiple domains of behavioral phenotypes in Nrgn KO mice using a comprehensive behavioral test battery including tests of homecage locomotor activity and nesting behavior. Methods Adult Nrgn KO mice (28‐54 weeks old) were subjected to a battery of comprehensive behavioral tests, which examined general health, nesting behavior, neurological characteristics, motor function, pain sensitivity, locomotor activity, anxiety‐like behavior, social behavior, sensorimotor gating, depression‐like behavior, and working memory. Results The Nrgn KO mice displayed a pronounced decrease in nesting behavior, impaired motor function, and elevated pain sensitivity. While the Nrgn KO mice showed increased locomotor activity in the open field test, these mice did not show hyperactivity in a familiar environment as measured in the homecage locomotor activity test. The Nrgn KO mice exhibited a decreased number of transitions in the light‐dark transition test and decreased stay time in the center of the open field test, which is consistent with previous reports of increased anxiety‐like behavior. Interestingly, however, these mice stayed on open arms significantly longer than wild‐type mice in the elevated plus maze. Consistent with previous studies, the mutant mice exhibited decreased prepulse inhibition, impaired working memory, and decreased sociability. Conclusions In the current study, we identified behavioral phenotypes of Nrgn KO mice that mimic some of the typical symptoms of neuropsychiatric diseases, including impaired executive function, motor dysfunction, and altered anxiety. Most behavioral phenotypes that had been previously identified, such as hyperlocomotor activity, impaired sociability, tendency for working memory deficiency, and altered sensorimotor gating, were reproduced in the present study. Collectively, the behavioral phenotypes of Nrgn KO mice detected in the present study indicate that Nrgn KO mice are a valuable animal model that recapitulates a variety of symptoms of neuropsychiatric disorders, such as schizophrenia, ADHD, and Alzheimer's disease.